2017
DOI: 10.1007/978-3-319-49562-0
|View full text |Cite
|
Sign up to set email alerts
|

Convection in Porous Media

Abstract: the material is concerned, specifically the rights of translation, reprinting, reuse of illustrations, recitation, broadcasting, reproduction on microfilms or in any other physical way, and transmission or information storage and retrieval, electronic adaptation, computer software, or by similar or dissimilar methodology now known or hereafter developed. The use of general descriptive names, registered names, trademarks, service marks, etc. in this publication does not imply, even in the absence of a specific … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

16
418
0
9

Year Published

2017
2017
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 605 publications
(443 citation statements)
references
References 0 publications
16
418
0
9
Order By: Relevance
“…Figure (3) is sketched in order to explore the variations of permeability parameter D. It is found that the magnitude of the velocity increases with increasing the values of permeability parameter D. This is due to the fact that increasing the permeability reduces the drag force which assists the fluid considerably to move fast. Likewise the magnitude of the velocity u reduced continuously with increasing the radiation parameter R from figure (4). The magnitude of the velocity enhances with increasing visco-elastic parameter  (Fig.…”
Section: Resultsmentioning
confidence: 73%
“…Figure (3) is sketched in order to explore the variations of permeability parameter D. It is found that the magnitude of the velocity increases with increasing the values of permeability parameter D. This is due to the fact that increasing the permeability reduces the drag force which assists the fluid considerably to move fast. Likewise the magnitude of the velocity u reduced continuously with increasing the radiation parameter R from figure (4). The magnitude of the velocity enhances with increasing visco-elastic parameter  (Fig.…”
Section: Resultsmentioning
confidence: 73%
“…Convection in porous media also is applied to underground coal gasification, ground water hydrology, iron blast furnaces, wall cooled catalytic reactors, solar power collectors, energy efficient drying processes, cooling of electronic equipment's and natural convection in earth's crust. Reviews of the applications associated to convective flows in porous media can be found in Nield and Bejan [7].The fundamental problems of flow through and past porous media has been studied extensively over the years both theoretically and experimentally by Cheng [8] and Rudraiah [9].The effect of Beavers-Joseph slip velocity and transverse magnetic field on an electrically conducting viscous fluid in a horizontal channel bounded on both sides porous substrates of finite thickness was studied Rudraiah et al [10], which is equivalent to the problem of forced convection where the momentum equation is independent of concentration distribution and the diffusion equation is coupled with the velocity distribution using BeaversJoseph slip condition at the porous interface. In many chemical engineering processes, the chemical reaction occurs between a foreign mass and the fluid in which the plate is moving.…”
Section: Introductionmentioning
confidence: 99%
“…A distinctive property of a porous medium is the spatial variability of its hydraulic properties, which controls the rate at which chemical species react and disperse in geological formations [1][2][3], heat transfer [4,5] and water plant uptake [6,7]. The heterogeneous structure of the porous medium induces deformation of the fluid material elements which leads to spatially erratic flow paths.…”
Section: Introductionmentioning
confidence: 99%